The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1097/cej.0b013e32832f9aa6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of fascin-1 and E-cadherin expression in laryngeal squamous cell carcinoma

Abstract: Fascin-1 and E-cadherin, both of which are related to cell motility and cell adhesiveness, are important factors in the progression and metastasis of cancers. The objective of this study was to explore the association between fascin-1 and E-cadherin expression levels with both the clinical characteristics and prognoses of patients with laryngeal squamous cell carcinoma; we did so through statistical analyses. In our study, tumor tissue samples from 150 patients with laryngeal squamous cell carcinoma were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 29 publications
4
39
0
Order By: Relevance
“…Since the overexpression of fascin has been well established in various human carcinomas examined to date [7][8][9][10][11][12][13][14][15][16], fascin has been identified as a new indicator of aggressive phenotypes and poor prognosis in malignant human epithelial carcinomas [7][8][9][10][11][12][13][14][15][16][17][18][19]. Besides its significance as an important tumor-promoting factor, convincing evidence also implicates fascin as a novel target for metastasis prevention [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the overexpression of fascin has been well established in various human carcinomas examined to date [7][8][9][10][11][12][13][14][15][16], fascin has been identified as a new indicator of aggressive phenotypes and poor prognosis in malignant human epithelial carcinomas [7][8][9][10][11][12][13][14][15][16][17][18][19]. Besides its significance as an important tumor-promoting factor, convincing evidence also implicates fascin as a novel target for metastasis prevention [10].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that fascin expression is quite low or absent in normal epithelial cells, while being significantly elevated in a variety of cancers [7][8][9][10][11][12][13][14][15], we believed that fascin expression could be induced by factors which could activate ERK1/2-Sp1 pathway. It was reported that both EGF and TGF-b1 induced target gene expressions through the activation of ERK1/2 and Sp1 [37,38].…”
Section: O N T R O L S I R N a S P 1 S I R N A 1 S P 1 S I R N A 2 mentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, high fascin expression has been correlated with low E-cadherin (epithelial cadherin) expression, indicating that as cells progress through the epithelial to mesenchymal transition (EMT), they gain fascin whilst losing E-cadherin. 27,28 There is evidence that fascin expression is regulated by the wnt activated LEF-TCF transcriptional signalling pathway that promotes EMT. 11 However, fascin expression is also regulated by cyclic-AMP response element binding protein (CREB) and the aryl hydrocarbon receptor (AhR).…”
Section: Why Is Fascin Special?mentioning
confidence: 99%